2019
DOI: 10.3390/met9050598
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Heterogeneous Nanostructures: A Strategy for Superior Mechanical Properties in Metals

Abstract: Generally, strength and ductility are mutually exclusive in homogeneous metals. Nanostructured metals can have much higher strength when compared to their coarse-grained counterparts, while simple microstructure refinement to nanoscale generally results in poor strain hardening and limited ductility. In recent years, heterogeneous nanostructures in metals have been proven to be a new strategy to achieve unprecedented mechanical properties that are not accessible to their homogeneous counterparts. Here, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 159 publications
(378 reference statements)
0
8
0
1
Order By: Relevance
“…Moreover, a simultaneously improvement in the strength and the uniform elongation is found at cryogenic temperature for the GS2 sample, as compared to the CG sample. According to the previous papers [30][31][32]59], excellent tensile properties can be achieved by heterogeneous structures due to the HDI hardening, which can be attributed to the back stress that arises from plastic deformation incompatibility between hard and soft domains. In the gradient structures, the various layers at different depths have various hardness and strain hardening ability; thus, these layers can be considered as hard and soft domains, and HDI hardening should play an important role during tensile loading for the gradient structures [31,60].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a simultaneously improvement in the strength and the uniform elongation is found at cryogenic temperature for the GS2 sample, as compared to the CG sample. According to the previous papers [30][31][32]59], excellent tensile properties can be achieved by heterogeneous structures due to the HDI hardening, which can be attributed to the back stress that arises from plastic deformation incompatibility between hard and soft domains. In the gradient structures, the various layers at different depths have various hardness and strain hardening ability; thus, these layers can be considered as hard and soft domains, and HDI hardening should play an important role during tensile loading for the gradient structures [31,60].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the case for metals with pronounced Bauschinger effects needs to be studied in association with the back stress (c.f., e.g. Ma et al , 2019; Zhu and Wu, 2019). In this case, anisotropic hardening and softening need be taken into account toward properly simulating finite rotation effects involved in shearing and twisting problems (cf., e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been postulated that only certain alloys, in which the development of recovery and recrystallization processes is hindered, may potentially offer the possibility of producing nanometric structure in the deformed material [ 21 ]. Examples include Mg-AZ31 alloys [ 21 ], austenitic steels [ 22 ], steel, Cu, Ni [ 23 , 24 ], Al7.5%Zn-2.7%Mg-2.3%Cu-0.15%Zr alloy [ 25 ], (Ni 1.5 FeCoCr 0.5 ) 87.5 Al 7.5 Ti 5.0 [ 26 ], Cu-Fe-P, Cu-Ni-Si, Cu-Cr-Zr [ 27 ]. Studies have shown that the formation of nanostructure is associated with an increase in the level of hardening (Ni 1.5 FeCoCr 0.5 ) 87.5 Al 7.5 Ti 5.0 .…”
Section: Introductionmentioning
confidence: 99%